Expert Consensus on Cognitive Dysfunction in Diabetes - Yang, Yan; Zhao, Jia-jun; Yu, Xue-feng (Current medical science, 2022)
The incidence of diabetes is gradually increasing in China, and diabetes and associated complications, such as cognitive dysfunction have gained much attention in recent time. However, the concepts, clinical treatment, and prevention of cognitive dysfunction in patients with diabetes remain unclear. The Chinese Society of Endocrinology investigated the current national and overseas situation of cognitive dysfunction associated with diabetes. Based on research both in China and other countries worldwide, the Expert Consensus on Cognitive Dysfunction in Diabetes was established to guide physicians in the comprehensive standardized management of cognitive dysfunction in diabetes and to improve clinical outcomes in Chinese patients. This consensus presents an overview, definition and classification, epidemiology and pathogenesis, risk factors, screening, diagnosis, differential diagnosis, treatment, and prevention of cognitive dysfunction in patients with diabetes.